2022
DOI: 10.1093/eurheartj/ehac617
|View full text |Cite
|
Sign up to set email alerts
|

Electrocardiogram-based deep learning improves outcome prediction following cardiac resynchronization therapy

Abstract: Aims This study aims to identify and visualize electrocardiogram (ECG) features using an explainable deep learning–based algorithm to predict cardiac resynchronization therapy (CRT) outcome. Its performance is compared with current guideline ECG criteria and QRSAREA. Methods and results A deep learning algorithm, trained on 1.1 million ECGs from 251 473 patients, was used to compress the median beat ECG, thereby summarizing m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…The predictive capacity of latent space variables for arrhythmia prediction reportedly outperforms standard ECG criteria and clinical interpretations, which indicates the ability of autoencoders to map unique prognostic ECG features to a latent representation not reflected by traditional ECG parameters. 17 , 18 , 20 , 21 The framework used in this study, which integrates an unsupervised learning branch (the autoencoder) and a supervised learning branch (the dynamic ML model), is related to the concept of digital twins , which create virtual replicas of individual patients by continuously integrating and analysing their real-time physiological data. 50 , 51 Despite the potential of deep learning networks to extract features from high dimensional data and aid clinical decision-making, the interpretability and explainability of neural networks remains a significant challenge and an active field of research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The predictive capacity of latent space variables for arrhythmia prediction reportedly outperforms standard ECG criteria and clinical interpretations, which indicates the ability of autoencoders to map unique prognostic ECG features to a latent representation not reflected by traditional ECG parameters. 17 , 18 , 20 , 21 The framework used in this study, which integrates an unsupervised learning branch (the autoencoder) and a supervised learning branch (the dynamic ML model), is related to the concept of digital twins , which create virtual replicas of individual patients by continuously integrating and analysing their real-time physiological data. 50 , 51 Despite the potential of deep learning networks to extract features from high dimensional data and aid clinical decision-making, the interpretability and explainability of neural networks remains a significant challenge and an active field of research.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have demonstrated encoder-decoder architecture neural networks to be able to extract physiologically-relevant ECG features in a latent feature space. 17 , 18 , 19 , 20 , 21 Considering that this latent space provides a comprehensive representation of the underlying ECG brought back to a pre-defined number of variables, it can be subsequently used for classification and regressions tasks. 22 In this study, we examine the potential of accommodating a supervised dynamic ML model with the learned low-dimensional representations from longitudinal ECGs spanning a duration of 44 months.…”
Section: Introductionmentioning
confidence: 99%
“…Highlighting significant segments in ECGs or visualizing decision-making in structured data sets can provide insights that can be interpreted based on mechanistic understanding. 170 , 177–180 Additionally, the availability of generic frameworks enables the visualization of decisions from various deep neural networks, making them applicable to multiple data sources, including structured data sets. 181 …”
Section: Artificial Intelligence In the Detection And Management Of A...mentioning
confidence: 99%
“…Artificial intelligence has found its usefulness in ECG for the following purposes: diagnosis of pulmonary thromboembolism [ 95 ], prediction of sudden death and cardiovascular events [ 97 , 98 ], prediction of fatal events after cardiac resynchronization [ 99 ], prediction of paroxysmal atrial fibrillation [ 37 ], detection of ventricular hypertrophy [ 100 ], risk prediction in liver transplantation [ 101 ], detection of ventricular dysfunction [ 103 ], and prediction of recurrence after paroxysmal atrial fibrillation ablation [ 38 ].…”
Section: Literature Reviewmentioning
confidence: 99%